2020
DOI: 10.21037/atm-20-5832
|View full text |Cite
|
Sign up to set email alerts
|

Association of high-risk human papillomavirus infection duration and cervical lesions with vaginal microbiota composition

Abstract: Background: Cervical cancer is reportedly caused by the synergistic effects of persistent high-risk human papillomavirus (HPV) infection. Cervical microbiota represent a unique and dynamically changing microecological system that is directly exposed to the vagina. The relationship between HPV and the composition of the cervical microbiome has long been a primary focus of research.Methods: To determine the specific differential florae throughout the process of cervical cancer development, in the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Third, excellent local environmental advantages have created healthy reproductive system microbes, which are good for resisting the damage of viruses to human cells, causing a lower incidence rate of CC with a lower infection rate. However, it is speculated that the specific vaginal and cervical microecology might affect HPV infection in the cervical epithelium and the outcome after infection in a specific manner (Liu et al, 2020). Therefore, it is necessary to deeply study local women's reproductive tract microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, excellent local environmental advantages have created healthy reproductive system microbes, which are good for resisting the damage of viruses to human cells, causing a lower incidence rate of CC with a lower infection rate. However, it is speculated that the specific vaginal and cervical microecology might affect HPV infection in the cervical epithelium and the outcome after infection in a specific manner (Liu et al, 2020). Therefore, it is necessary to deeply study local women's reproductive tract microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the physiological structure of the cervix and vagina, imbalance in the vaginal microecosystem directly increases the chance of HPV infection and accelerates the process of cervical precancerous lesions (Kovachev, 2020). Vaginal health is more commonly associated with low microbial diversity (Laniewski et al, 2020;Liu et al, 2020;Nunn et al, 2020), and there are some differences among the population. The reasons for these observed differences among ethnic groups are unknown, but it is tempting to speculate that the species composition of vaginal communities could be governed by genetically determined differences between hosts (Zhou et al, 2007;Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study (DI Pierro et al, 2021) demonstrated for the first time that oral Lactobacillus curlicus can change the state of CST and increase HPV clearance. Persistent high-risk HPV infection and changes in cervical microenvironment promote the development of cervical precancerous lesions (Liu et al, 2020). Lactobacillus activates the immune system to inhibit the proliferation of malignant tumors by secreting various a n t i t u m o r m e t a b o l i t e s , in c l u d i n g p h o s p ho r y l a t e d polysaccharides and extracellular polysaccharides.…”
Section: Probiotics and Cervical Cancermentioning
confidence: 99%
“…Though HPV infection can orchestrate immune responses and then affect CVM structures, VM-host interactions keep existed before HPV infection and thus impose momentous effect on persistence of stochastic HPV infection via VMmodulated host responses (Anahtar et al, 2015). In consistence, several studies indicated significant CVM differences between women with clearance of HPV infection and those with persistent infection (Di Paola et al, 2017;Berggrund et al, 2020;Liu et al, 2020;Mitra et al, 2020;Usyk et al, 2020). In addition, longitudinal studies indicated the vital impact of CVM on persistence of HPV infection (Mitra et al, 2020;Usyk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%